STUDI KRITIK TERHADAP PEMIKIRAN KH. AHMAD DAHLAN DALAM PENENTUAN ARAH KIBLAT DAN AWAL BULAN QAMARIYAH - Munfaridah, Imroatul (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
This study seeks to reveal and explain the thinking of KH. Ahmad Dahlan about the direction of Qibla, the beginning of the month Qamariyah and the extent of the influence of KH. Ahmad Dahlan in Muhammadiyah related to astronomy.This study uses the approach of astronomy (falaq) or astronomy that are characteristic of astronomy research is supported by interviews and documentation to obtain representative data. These approaches can be found the results, namely: First, KH. Ahmad Dahlan able to create a theory to determine the direction of Qibla ie using a globe, which was not yet so advanced technology, with a globe that KH. Ahmad Dahlan diligence that the direction of the Qibla of Yogyakarta city in general and in particular the Great Mosque is 240, when compared with the contemporary direction of qibla calculation software is less oblique to the right 1 15 '0